2023
DOI: 10.1172/jci171268
|View full text |Cite
|
Sign up to set email alerts
|

CFTR-rich ionocytes mediate chloride absorption across airway epithelia

Abstract: The volume and composition of a thin layer of liquid covering the airway surface defend the lung from inhaled pathogens and debris. Airway epithelia secrete Cl – into the airway surface liquid through cystic fibrosis transmembrane conductance regulator (CFTR) channels, thereby increasing the volume of airway surface liquid. The discovery that pulmonary ionocytes contain high levels of CFTR led us to predict that ionocytes drive secretion. However, we found the opposite. Elevating ionocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…With regard to the distribution of ionocytes, direct whole mount tissue analysis of dissected large and small airways identified the presence of CFTR-rich distal ionocytes in indistinguishable numbers along the proximodistal axis of the human airway tree. Recently, experiments in which ionocytes were genetically ablated in the ferret led to aberrant airway surface physiology mirroring the abnormalities seen in CF 12 while the loss of human ionocytes led to abnormalities of ion transport in vitro 14 . Taken together, this suggests that human ionocytes likely play a role in the pathogenesis of both large and small airways disease in CF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the distribution of ionocytes, direct whole mount tissue analysis of dissected large and small airways identified the presence of CFTR-rich distal ionocytes in indistinguishable numbers along the proximodistal axis of the human airway tree. Recently, experiments in which ionocytes were genetically ablated in the ferret led to aberrant airway surface physiology mirroring the abnormalities seen in CF 12 while the loss of human ionocytes led to abnormalities of ion transport in vitro 14 . Taken together, this suggests that human ionocytes likely play a role in the pathogenesis of both large and small airways disease in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ionocytes express the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR), the causal gene whose disruption leads to cystic fibrosis (CF) 6,7 . Indeed, their ablation in a ferret model of CF has recently been shown to result in abnormalities of airway physiology remarkably reminiscent of CF, and their loss in human large airway epithelial cultures disrupts ion transport 12–14 . In contrast, tuft cells and NE cells have roles in environmental sensing and initiating inflammatory responses 7,15 .…”
Section: Mainmentioning
confidence: 99%
“…High levels of CFTR expression in ionocytes would suggest an increase in the volume of ASL due to ionocyte liquid secretion. Nonetheless, Lei and coworkers observed an increase in liquid absorption, and consequently a decrease in ASL volume in ionocyte-rich cultures, while a reduction in ionocyte abundance led to an increased liquid secretion ( Lei et al, 2023 ). A possible explanation for that is the presence of basolateral barttin/Cl − channels in ionocytes.…”
Section: Cell Type-specific Regulation Of Cftrmentioning
confidence: 99%
“…It is of interest that CFTR proteins are abundantly expressed in forkhead box I1 (FOXI1)-positive pulmonary ionocytes ( Montoro et al, 2018 ; Plasschaert et al, 2018 ), while airway epithelia of FOXI1-knockout mice display increased ciliary beat frequency and mucus viscosity ( Montoro et al, 2018 ). Lei et al ( Lei et al, 2023 ) demonstrated that apical membrane CFTR Cl − channels collaborate with basolateral membrane barttin/ClC-K Cl − channels in ionocytes for transepithelial Cl − absorption, leading to fluid absorption. Moreover, FOXI1-knockout and CF ferrets both display reduced ASL volume and impaired mucociliary clearance due to ASL abnormalities, including slow fluid absorption but also absent fluid secretion, lack of CFTR-mediated ASL alkalization and increased mucus viscosity ( Yuan et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, FOXI1-knockout and CF ferrets both display reduced ASL volume and impaired mucociliary clearance due to ASL abnormalities, including slow fluid absorption but also absent fluid secretion, lack of CFTR-mediated ASL alkalization and increased mucus viscosity ( Yuan et al, 2023 ). Therefore, albeit less than about 1% of total epithelial cells in airways ( Montoro et al, 2018 ; Plasschaert et al, 2018 ; Lei et al, 2023 ), ionocytes regulate ASL homeostasis. However, whether the dysfunction of ionocytes contributes to the pathogenesis of CF lung diseases needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%